An evolutionary case for polygyny to counter demographic collapse - Larsen, Mads (Frontiers in Psychology, 2023)
Sex ratio theory suggests why mating practices have become dysfunctional in the West and other regions. Spain, Japan, and over 20 other nations are on course to have their populations halved by 2100, dramatically aging their citizenry. Experts and opinion makers warn that a demographic collapse cannot be absorbed by our current social order; Elon Musk proclaims this to be “the biggest threat to human civilization.” Statistics from the Nordic countries—the world’s most gender-equal region—indicate that subjective perceptions of the sex ratio in modern environments drive singledom and low reproduction. Scandinavia has the world’s highest occurrence of one-person households: 43–46%. In the past decade, the Norwegian fertility rate dropped from 2.0 to 1.5. Sex ratio studies suggest that women’s perception of there being few acceptable partners activates a polygynous mindset, which in prosperous, monogamous societies drives promiscuity to the detriment of pair-bonding. More than 6 million years of hominin evolution under promiscuous, polygynous, and monogamous regimes shaped mate preferences that evoke different cultural and behavioral responses as environments change. The Church’s imposition of lifelong monogamy contributed to the emergence of the modern world, but if this world’s gender-equal societies no longer motivate reproduction, being more open to polygyny could be worth considering as a means for increasing fertility. This article makes this case by exploring hominin mating from our last common ancestor with chimpanzees—through the genus Homo’s forager and agricultural periods—to modern Scandinavians. In the past millennium, mating practices have coevolved with the emergence of modernity, necessitating frequent cultural updates. An evolutionary analysis of Nordic works of literature illuminates the ways in which ideological narratives influence reproductive norms. The insights gleaned are considered in the context of people’s perceived sex ratio.